TASAWWUF mystical thought, practice and experience of selected Tausug practitioners - Ismael, Timhar H.; Wadi, Julkipli M. (Quezon City Institute of Islamic Studies, University of the Philippines Diliman, 2007)
This work is a study of the influence of Tasawwuf among Tausug.It focuses on Tausug mystical thought, practice and experience.
Thesis (M.A. Islamic Studies)--University of the Philippines Diliman
Keywords: Islam -- Doctrines; Tausug (Philippine people) -- Philippines -- Mindanao